2016
DOI: 10.1209/0295-5075/115/13001
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Lifshitz forces and gas on premelting of ice within porous materials

Abstract: -Premelting of ice within pores in earth materials is shown to depend on the presence of vapor layers. For thick vapor layers between ice and pore surfaces, a nanosized water sheet can be formed due to repulsive Lifshitz forces. In the absence of vapor layers, ice is inhibited from melting near pore surfaces. In between these limits, we find an enhancement of the water film thickness in silica and alumina pores. In the presence of metallic surface patches in the pore, the Lifshitz forces can dramatically widen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…[31], Dash et al thoroughly reviewed a related phenomenon of the premelting of ice, which was also considered by some of us in Ref. [32] where we showed that it is essential to have a vapor layer between ice and a silica surface to have premelting of the ice. )…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…[31], Dash et al thoroughly reviewed a related phenomenon of the premelting of ice, which was also considered by some of us in Ref. [32] where we showed that it is essential to have a vapor layer between ice and a silica surface to have premelting of the ice. )…”
mentioning
confidence: 65%
“…In real systems, optical properties, surface charges, surface roughness [3], the density of the material, gravity [28,52], ions [40,53,54], the presence of gas layers on ice premelting in pores [32] and so on influence the total energy of the system. It is an advantage of the theory that different properties can be analyzed separately.…”
mentioning
confidence: 99%
“…[10] In a similar way, the premelting water layer thickness for ice in cavities can be enhanced by the presence of a gas layer between ice and the pore surface. [11] Additional effects can potentially arise from ion-specific hydration and ion-specific dispersion forces between ions and interfaces, [12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…We investigate the thickness dependences on the solid layer using an extended thickness model. 45 We consider therefore a vertically oriented layer-structure, and that the solid slab is able to move (or float) up and down in the liquid, and the slab feels the buoyancy pressure. This can thus be regarded as a four-layer system tin/liquid/solid/liquid containing a thin solid layer (typically SiO 2 ) with the finite thickness d in a liquid (typically Bb in mixture with Cb).…”
Section: Results: Finite Size Silica Layermentioning
confidence: 99%